(Des) proteção de dados e internet das coisas: os desafios à tutela dos dados de saúde de usuários de dispositivos de IOT à luz dos preceitos da LGPD - Ruviaro, Eduardo Missau (2021)
The present work investigates what is the contribution given by the General Law of Protection of Personal Data, in Brazil, for the protection of the risks to which the users of applications connected to the internet of the things that use tools that capture health data are exposed. Does LGPD act preventively or remedially to the potential damage caused by the capture of health data by IoT applications? We sought, deductively, to point out how the concept of internet in the world evolved, with the emergence of the internet of things within the context of the fourth generation of the web. It was conceptualized what is the internet of things, what are the facilities brought by applications connected to the IoT as a theme, and the risks to which the users of these devices, especially those that capture sensitive personal health data, as a problem. The weighing of this theme and this problem, which culminated in a risk society, deductively made it necessary for the emergence of protective norms of personal data, in order to protect the right of data subjects in the face of applications connected to the IoT. The emergence of the said generations of protective data standards was described, from its first generation to the LGPD at the height of the fourth phase of protective standards. It was observed, therefore, that, in the fourth generation of norms, informative self-determination, made positive by the legal basis of consent, made LGPD unable to protect the rights of holders of sensitive personal health data, in addition to the vagueness of the positive provisions and the reprimand of the guided administrative sanctions. As for the methodology, the deductive approach method was used, starting from the evolution of the concept of internet and internet of things, under the theoretical framework of Castells and Magrani, passing through Ulrich Beck's risk society, passing through the emergence and due to the importance of data protection rules, under the doctrine of Doneda and Viktor Mayer-Schöenberger, to which the research problem can be answered, in the last topic of the text. As a result, the repressive, and not preventive, link of the General Data Protection Law was pointed out, in the protection of the misuse of sensitive personal health data collected from IoT applications, in addition to the insufficiency of the legal basis of consent and vagues. specific legal bases, enabling the processing and sharing of said personal data.